Fatigue in person with sequels of COVID-19, a proposal for rehabilitation: Case Study - Filipa Barbosa; Paula Figueiredo; Ana Cristina Nunes Mesquita Mesquita; Helena Pestana (Associação Portuguesa dos Enfermeiros de Reabilitação, 2022)
Background: COVID-19 can cause persistent sequelae, being fatigue the most described. Specialist nurses in rehabilitation nursing have specialized knowledge in the control and reduction of fatigue. Objective: It is intended to identify the gains sensitive to respiratory rehabilitation in the focus of ventilation and activity intolerance; analyze the effort tolerance in the person after infection with-COVID-19 and verify the effectiveness of the interventions of the specialist nurse in rehabilitation nursing in the control and reduction of fatigue in people with sequelae of COVID-19. Method: Case study with quantitative and qualitative data collection. We present the case of a person with post-COVID sequelae and muscle weakness acquired in intensive care, characterized by ineffective ventilation and activity intolerance. Results: The nursing process, integrated the respiratory rehabilitation recommendations of the Chinese Society of Rehabilitation Medicine. With 14 rehabilitation sessions, it was found: reduced fatigue, increased vital capacity, and increased distances covered and increased autonomy in performing ADLs. Conclusions: With the implementation of an individualized rehabilitation nursing care plan, it is possible to act in the control and reduction of fatigue in people with sequelae of COVID-19, providing health gains that are sensitive to the care of rehabilitation nursing care.